Short-Term Outcomes and Predictors of Effectiveness of Tocilizumab in Systemic Juvenile Idiopathic Arthritis: A Prospective Cohort Study - Nada, Doaa W.; Moghazy, Abdelkawy; Allam, Abdallah El-Sayed; Alunno, Alessia; Ibrahim, Amira M. (Frontiers in Medicine, 2021)
Background: Systemic Juvenile Idiopathic Arthritis (sJIA) is a unique category of juvenile arthritis in which interleukin 6 plays a major pathogenic role. This study aimed to describe the therapeutic short-term outcomes among patients with sJIA starting tocilizumab (TCZ) therapy and to identify possible predictors of treatment response. Methods: We conducted a prospective observational study including 65 patients with sJIA meeting ILAR classification criteria with active disease despite conventional therapy that were treated by TCZ between August 2019 and October 2020 as the first-line biological therapy. Clinical and serological parameters were recorded at baseline and after 1 year of TCZ therapy. Results: After 1 year, 25% of the patients achieved minimal disease activity and 35% achieved clinically inactive disease. A significant reduction of the 10-joint juvenile arthritis disease activity score and acute phase reactants was also observed. Patients with younger age (≤7 years), shorter disease duration (≤3 years), lower disease activity, and higher serum ferritin and systemic manifestations showed more favorable results. Conclusion: Patients with sJIA showed favorable disease outcomes with TCZ treatment for 1 year, especially if the drugs were administered earlier in the disease course and in younger patients with a more pronounced inflammatory status. Our results may help to define the profile of patients with sJIA who are more likely to benefit from IL-6 blockade.